(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
This study represents an attempt to reduce the drying time of wet grain wheat of the fluidized bed dryer (FBD), using straight blades, and debates the effect of stirrer on the whole drying time at different static bed heights. Experiments for FBD were conducted at the low velocity of air supply (1.45 cm/s) with moisture content for grain wheat 12% and ambient temperature of 37°C for each static bed height (9, 12, and 15 cm). FBD was made from a glass cylindrical column with inside diameter 4.6 cm, outside diameter (5.2 cm) and length (116 cm). The results showed an enhancement of (12- 20.5%) in the total drying time for bed height (9 and 15) cm, respectively. Also, increasing bed height from 9 cm to 15 cm possesses no influence on the equilibrium content of moisture in both techniques of drying either stirred fluidized bed or conventional fluidized bed.